A Comparison of Low‐Income Versus Higher‐Income Individuals Seeking an Online Relationship Intervention. Issue 4 (29th October 2019) - Williamson, Hannah C.; Nguyen, Thao T. T.; Rothman, Karen; Doss, Brian D.
Abstract : Compared to higher‐income couples, low‐income couples experience higher rates of relationship disruption, including divorce and breakup of cohabiting relationships. In recognition of this disparity in relationship outcomes, relationship interventions have increasingly been targeted at this population. However, these interventions have had limited impacts on the relationships of low‐income couples. Developing interventions that are effective and responsive to the needs of low‐income couples requires descriptive data on the challenges those couples perceive in their own relationships and an assessment of how their needs compare to the more affluent couples typically served by relationship interventions. The current study sampled over 5, 000 individuals at the time they were seeking an online relationship intervention and compared the relationship functioning and life circumstances reported by low‐income individuals to that of higher‐income individuals. Results indicate that low‐income individuals seeking a relationship intervention had higher levels of relationship distress (lower relationship satisfaction, more intense primary relationship problems, and less relationship stability), and had greater levels of contextual stress (more children living at home, less likely to be employed full‐time, and lower levels of perceived health). Results suggest that future interventions designed to target low‐income couples, as well as practitioners working with low‐income couples, should be prepared to handle higher levels of relationship distress and contextual stressors than they may typically see in more affluent couples. Abstract : En comparación con las parejas de recursos más altos, las parejas de bajos recursos tienen índices altos de dificultades en las relaciones, incluidos el divorcio y la ruptura de las relaciones de convivencia. En reconocimiento de esta disparidad en las consecuencias de las relaciones, se han destinado cada vez más a esta población intervenciones en las relaciones. Sin embargo, estas intervenciones han tenido efectos limitados en las relaciones de las parejas de bajos recursos. El desarrollo de intervenciones que sean eficaces y sensibles a las necesidades de las parejas de bajos recursos exige datos descriptivos sobre las dificultades que esas parejas perciben en sus propias relaciones y una evaluación de cómo sus necesidades se comparan con las de las parejas más pudientes que normalmente reciben intervenciones en las relaciones. El presente estudio tomó muestras de más de 5000 personas en el momento en que estaban buscando una intervención en las relaciones por internet y comparó el funcionamiento de las relaciones y las circunstancias de vida informadas por personas de bajos recursos con las de personas de recursos más altos. Los resultados indican que las personas de bajos recursos que buscaban una intervención en las relaciones tenían niveles más altos de distrés relacional (una menor satisfacción con las relaciones, problemas más intensos en las relaciones principales y menos estabilidad relacional) y tenían niveles más altos de estrés contextual (más niños viviendo en la casa, menos probabilidades de estar empleados tiempo completo y niveles más bajos de salud percibida). Los resultados sugieren que las futuras intervenciones diseñadas para las parejas de bajos recursos, así como los profesionales que trabajan con estas parejas deberían estar preparados para manejar niveles más altos de distrés relacional y factores de estrés contextual que los que pueden ver normalmente en las parejas más pudientes. Abstract : 和高收入的伴侣相比, 低收入伴侣之间的关系解体的比率要高得多, 这种伴侣关系瓦解包括离婚和与同居的伴侣分手。认识到关系干预措施对关系发展的结果能造成差异, 相关措施越来越多地针对此类人群使用。然而, 这些干预对低收入伴侣的关系的影响却非常有限。面向低收入伴侣的关系干预措施要想有效且能对其需求有针对性回应, 就需要描述类的数据, 这些数据能反映这些伴侣自己如何看待他们关系出现的问题, 以及和高收入的伴侣使用的代表性的干预措施比起来, 他们如何评估他们自己的需要。本研究的样本来自网上招募的5, 000个个体, 他们在网上寻求关系干预, 他们也比较低收入伴侣和较高收入伴侣这两类人群的关系状况和生活状况。结果表明低收入伴侣寻求关系干预时, 关系经历着更高水平的痛苦(较低的关系满意度、主要关系问题更严重、关系稳定性也较差), 整个生活境况也出现更高水平的紧张程度 (更多孩子在家生活、更不可能有全职的工作、健康状态堪忧)。结果表明在未来开发设计的干预措施应该着眼于低收入伴侣的需求, 那些治疗低收入伴侣的医师也都要有准备去处理更高水平的关系紧张程度, 导致他们生活环境紧张的多重因素, 而这些是平日治疗更富足的伴侣时不常见的。